Effect of vesicles of dimethyldioctadecylammonium chloride and phospholipids on the rate of decarboxylation of 6-nitrobenzisoxazole-3-carboxylate - Scarpa, M. V.; Araujo, P. S.; Schreier, S.; Sesso, A.; Oliveira, Anselmo Gomes de [UNESP]; Chaimovich, H.; Cuccovia, I. M. (Amer Chemical Soc, 2000)
Sonicated mixtures of dimethyldioctadecylammonium chloride (DODAC), egg phosphatidylcholine (PC), dimyristoyl phosphatidylcholine (DMPC), and dipalmitoyl phosphatidylcholine (DPPC) were used to analyze vesicle effects on the rate of decarboxylation of 6-nitrobenzisoxazol-3-carboxylic acid (Nboc). Electron microscopic images of the vesicles were obtained with trehalose, a know cryoprotector. Phase diagrams and phase transitions temperatures of the vesicle bilayers were determined. Nboc decarboxylation rates increased in the presence of vesicles prepared with both phospholipids and DODAC/phospholipid mixtures. Quantitative analysis of vesicular effects was done using pseudophase models. Phospholipids catalyzed up to 140-fold while the maximum catalysis by DODAC/lipid vesicles reached 800-fold. Acceleration depends on alkyl chain length, fatty acid insaturation of the lipids, and the DODAC/phospholipid molar ratio. Catalysis is not related to the liquid crystalline-gel state of the bilayer and may be related to the relative position of Nboc with respect to the interface.